Konsep Pendidikan Ketamadunan Pengakap (The Scouting Civilization Education) - Harry Ramza; Afri Yordan; Sofiyahna Kubro; Kaharudin Mokmin; Rusmiati Harun; Aslinda Aslinda (Fikiran Masyarakat, 2015)
The Educational Scouting Civilization is an educational process based on scout education which aims to improve the living conditions of civilization or society outwardly and spiritually. In Arabic, the meaning of civilization as same as "mudun", "madain" and "madani or civil society" that means a high polish, the opening of the city - the new city. The concept of education is based Al - Quran and the Sunnah of the Prophet Muhammad to the success of this world and the hereafter. Education process carried out with many handicaps such as; personal scouting ambition as a moslem scouting noble, active and fresh as the human body is beneficial to the country, the leadership soul of the moslem as high standing peoples, the life adventure as human responsibility to God and tobe Khalifa over the world. Standard competences of subject to be owned in the education concept are religion and morality, nationality and personality, science and technology, aesthetic, sport and health. Standard competence must be applied at the level of primary and secondary schools to achieve of successful outcomes of human resources.